A meta‐analysis of Tier 2 interventions implemented within School‐Wide Positive Behavioral Interventions and Supports. Issue 1 (24th October 2020) - Cho Blair, Kwang‐Sun; Park, Eun‐Young; Kim, Won‐Ho
Abstract: This meta‐analysis synthesized 26 published single‐case design (SCD) studies on Tier 2 behavior interventions implemented within the educational framework of school‐wide positive behavioral interventions and supports. We used Tau‐ U indices to determine the overall magnitudes of effect of the Tier 2 behavior interventions and the potential variables that moderate improved student behavioral outcomes. The 26 studies that were analyzed included a total of 243 student participants. The studies were evaluated to determine whether and to what extent they met What Works Clearinghouse (WWC) SCD standards. Of these, 10 studies were confirmed as meeting WWC SCD standards with or without reservations. Notable findings were that outcomes for students in kindergarten and secondary grade levels were limited, and insufficient screening methods were used to identify and select students needing Tier 2 interventions. The results indicate that the literature reports Tier 2 interventions with effect sizes ranging from 0.26 to 0.98. Average effect size for social skills instruction was found to be large, whereas Check‐in/Check‐out, group contingency, and intervention packages had medium effect sizes. Moderator analyses indicated different effect sizes across intervention types, outcomes, and implementers. The results are discussed in relation to implications for practice, limitations, and future research.